Spectres of Marx: The State of the Debt, The Work of Mourning & the New International - Derrida, Jacques (Routledge, 1994)
In the wake of the fall of communism, many in the west had become triumphalist, forgetting in their celebration that never before in the history of mankind, such suffering had bee seen at the hands of liberal democratic and capitalist ideology.
English
Keywords: B808-849- Philosophy- By Period- Modern- Special Topics and Schools of Philosophy; Marxism- manifestations